PERAN PEMERINTAH PUSAT DALAM MEMPERKUAT DESENTRALISASI: KASUS JEPANG DAN PELAJARAN UNTUK INDONESIA (THE ROLE OF CENTRAL GOVERNMENT IN STRENGTHENING DECENTRALIZATION: CASE STUDY OF JAPAN AND LESSONS FOR INDONESIA) - Tri Widodo W. Utomo (Jurnal Borneo Administrator, 2014)
The role of central government in strengthening sub-national governments is unquestionably vital. Principally, the central government also determines the degree of decentralization in a country. This paper tries to explore the role of central government in Japan in promoting local development through decentralization. There are some lessons that might adopted to build decentralization in Indonesia effectively. Firstly, central government needs to reinforce its commitment to transfer more powers to local government, and to reduce its intervention over local regulations. Secondly, the new framework of decentralization should oblige central government to provide economical incentive system in order to promote competition among local governments.Keywords: decentralization, role of central government, Japan, Indonesia.Tidak diragukan lagi bahwa peran pemerintah pusat dalam memperkuat pemerintah daerah sangat penting. Tingkat desentralisasi di suatu negara sangat ditentukan terutama oleh Pemerintah Pusat. Tulisan ini mencoba untuk mengeksplorasi peran pemerintah pusat di Jepang dalam mempromosikan pembangunan daerah melalui desentralisasi. Ada beberapa pelajaran yang mungkin dapat diadopsi untuk membangun desentralisasi yang lebih efektif di Indonesia. Pertama, Pemerintah Pusat perlu memperkuat komitmennya untuk mentransfer kewenangan yang lebih besar kepada pemerintah daerah, dan mengurangi intervensi atas peraturan atau regulasi daerah. Kedua, kerangka baru desentralisasi perlu mewajibkan pemerintah pusat untuk memberikan sistem insentif ekonomi dalam rangka mempromosikan kompetisi antar pemerintah daerah.Kata Kunci : desentralisasi, peran pemerintah pusat, Jepang, Indonesia.